Students’ Syntax Error In Writing Ability - Rulik Setiani (Universitas Muhammadiyah Kotabumi, 2017)
Writing is one of the language skills that must be mastered by students. By writing students can pour their ideas, opinions, and thoughts in writing. However, there are still some students who make mistakes in writing activities, especially writing English text. errors that are often done by students in writing English text is a misuse of syntax that is divided into errors in phrases, clauses, and sentences.